Construction and Evaluation of Recombinant Adenovirus Candidate Vaccines for Chikungunya Virus - Liang Cao; Wei Wang; Wenchao Sun; Jinyong Zhang; Jicheng Han; Changzhan Xie; Zhuo Ha; Yubiao Xie; He Zhang; Ningyi Jin; Huijun Lu (Viruses, 2022)
Chikungunya virus (CHIKV) is a mosquito-borne virus. The emergence of CHIKV infection has raised global concern, and there is a growing need to develop safe and effective vaccines. Here, adenovirus 5 was used as the vaccine vector to construct recombinant adenoviruses expressing CHIKV E2, E1, and E2-6K-E1, respectively. And then the immunogenicity and protective efficiency against CHIKV were evaluated in BALB/c mice. Compared to the ad-wt control group, all three vaccines elicited significant humoral and cellar immune responses. The levels of neutralizing antibodies in the rAd-CHIKV-E2-6K-E1 and rAd-CHIKV-E2 groups both reached 1:256, which were 3.2 times higher than those in the rAd-CHIKV-E1 group. Furthermore, the levels of lymphocyte proliferation in rAd-CHIKV-E2-6K-E1 group were the highest. Besides, the concentrations of IFN-γ and IL-4 in mice immunized with rAd-CHIKV-E2-6K-E1 were 1.37 and 1.20 times higher than those in ad-wt immunized mice, respectively. After the challenge, mice in the rAd-CHIKV-E2-6K-E1 and rAd-CHIKV-E2 groups lost 2% of their body weight compared with 5% in the ad-wt control group. And low viral loads were detected in the heart, kidney, and blood of mice immunized with rAd-CHIKV-E2-6K-E1 and rAd-CHIKV-E2 at 3–5 dpc, which decreased by 0.4–0.7 orders of magnitude compared with the ad-wt control. Overall, these data suggest that the recombinant adenovirus is a potential candidate vaccine against CHIKV.